TECHNOLOGICAL ROADMAP OF THE PUBLISHING MARKET: A PATH FOR UNIVERSITY PUBLISHERS OF THE NORTHEAST - Lessa de Santana, Mariana (2025)
There has been a disruption in the cultural market in the last three decades, due to marked technological transformations. Physical media began to be digitized. In the editorial world, processes underwent transformations following the launch of reader gadgets, transforming them into appropriate tools for consuming academic or entertainment information. In this scenario, part of the University Publishers remained under observation, but changes in relationships with consumers, such as those arising during the Covid-19 pandemic, encouraged an increase in digital releases. Investigating the difficulties encountered by University Publishers in the Northeast in following the evolution of technologies used in the publishing market, this work sought to develop a technological roadmap, between 2007 and 2022, in order to understand the appropriate business model for University Publishers in the region. In order to achieve these objectives, a methodology was created based on the analysis of patents in several international and national patent bodies, seeking to identify future trends. The results of the roadmap, between 2007 and 2022, point to the development, in recent years, of electronic book sales service platforms and the construction of virtual libraries and shelves, which makes it opportune to develop an electronic platform via an app that provides the demands of University Publishers to provide new interaction and consumption technologies for users increasingly accustomed to the digitalization of services.